Privatization in Developing Countries : An Analysis of the Performance of Newly Privatized Firms - Boubakri, Narjess; Cosset, Jean-Claude (World Bank, Washington, DC, 2012)
The privatization efforts of most developing countries are inhibited by embryonic financial markets, weak regulatory capacity, and a public sector that accounts for a large share of GDP. Many, particularly those with low per capita income, lack some of the main ingredients for a successful privatization, such as capital, entrepreneurs, and competent managers. But some of these countries have large markets and fast economic growth rates, features that make the success of government divestiture more likely. This Note describes the results of a study that set out to determine whether privatization is beneficial in the economic environments and institutional settings of these countries by examining how privatization affects firms' financial and operating performance in a broad set of developing countries.